Killing Eve. Season two [videorecording (DVD)] - Thomas, Damon; Brühlmann, Lisa, 1981-; Oh, Sandra, 1971-; Comer, Jodie, 1993-; Shaw, Fiona, 1958-; Jennings, Luke (BBC, 2019)
Eve, a deskbound MI5 agent who is recruited for MI6, becomes obsessed with a talented, young assassin.